(untitled) (Bangladesh Journal of Medical Science, 2012)
After traumatic injuries the pulps of young permanent teeth often necrose. This occurs most commonly in the permanent maxillary incisors leaving the teeth with incomplete radicular development and open apices. In these cases treatment is aimed at promoting complete apical closure. At a later date a complete filling of the root canal is carried out in order to prevent inflammatory stimulators affecting the periapex. Apexification is a method of treatment intended to induce formation of a calcific barrier in an immaturely developed or pulpless tooth. The intent of apexification is to attain narrowing of the canal or closure of the apex. Apexification is indicated in young patients, for reasons such as trauma, fracture or caries involving the pulp require root canal treatment prior to the apex fully developing and closing. DOI: http://dx.doi.org/10.3329/bjms.v11i2.11483 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 143-147